The Jurisprudence of University Lecturers’ and Students’ Knowledge of Nigerian Education Laws - Adeyemi Oyedele Omodele; Stella Ijeoma Ahunanya (Indonesian Journal of Education and Social Sciences, 2023)
This study investigates the university lecturers’ and students’ knowledge of Nigerian Education Laws which brings peace, progress, tranquility, and development to an academic environment with a view to find out how lecturers and students are knowledgeable about Nigerian Education Laws. It juxtaposes knowledge of education laws by lecturers and that of the students. It will be of benefit to students, lecturers, the education communities where education law is useful and applicable. It will be of benefit to the law community - the lawyers, judges, lecturers, students among others. Curriculum developers, education administrators, the National Universities Commission, the Federal Ministry of Education and its parastatal/agencies and the public will benefit from this work. Historical and case study designs were adopted. The doctrinal method was used in data collection. The primary sources of data were the Education Ordinance 1887, Education Code 1903, Education Ordinance 1928, Education Ordinance 1916, Education Code 1926, Education Ordinance 1948, Education Act 1952, Education Edicts 1966-1979, the Constitution of the Federal Republic of Nigeria 1979 and 1999, Education Law 1999 and the Universal Basic Education Act 2004; sources of secondary data were published textbooks, scholarly peer-reviewed journals, and articles. Data were content-analysed, compared, contrasted and presented thematically which brought about the relevance of the study. The research findings are that lecturers and students have knowledge of Nigerian Education Laws and that knowledge of Nigerian Education Laws makes lecturers and students conduct themselves within the purview of the rules and regulations of the institutions.  It is recommended that knowledge of Nigerian Education Laws should be a continuous exercise in an academic environment. Lecturers and students should be trained and retrained in respect of the education laws to avoid any gap in the level of knowledge of Nigerian Education Laws.